Six new Dinotrema species (Hymenoptera, Braconidae) from Spain, with prescutellar pit and medially sculptured propodeum - Peris-Felipo, Francisco Javier; Belokobylskij, Sergey A.; Jiménez-Peydró, Ricardo (Zootaxa, 2013)
Descriptions of six new species of the genus Dinotrema from Spain with smooth or only medially sculptured propodeum are provided. The new species described are: D. achterbergi sp. nov., D. broadi sp. nov., D. enanum sp. nov., D. fischerianum sp. nov., D. munki sp. nov. and D. pappi sp. nov.